Effect of GnRH treatment following a short-term estrous induction protocol on estrus and ovulation in Saanen goats, during the transitional period - DOGAN, I.; TOKER, M. B.; ALCAY, S.; UDUM KUCUKSEN, D. (Journal of the Hellenic Veterinary Medical Society, 2021)
The objective of this study was to compare the effect on the ovulation time and estrus parameters of a GnRH agonist (buserelin acetate) administered 24 or 36 h following a short-term estrus induction and synchronization treatment in non-lactating Saanen goats during the transitional period. Goats received 20 mg FGA sponges for 6 days plus 300 IU eCG and 125 μg d-cloprostenol 24 h prior to sponge removal. After removal of the sponges, goats were given either 1 ml physiological saline (0.9% NaCI) solution (Group1; n = 9) after 12 h, 0.004 mg GnRH (Group2; n = 10) after 24 h or 0.004 mg GnRH (Group3; n = 10) after 36 h. The follicle development and ovulation in the ovaries were monitored by transrectal ultrasonography starting from the sponge application until the fifth day of the estrus cycle. Blood samples were collected on the same days to determine the plasma concentrations of progesterone (P4) and estradiol (E2). No statistical differences among groups were detected in any synchronization parameters, ultrasonic evaluations and plasma P4 and E2 concentrations. The evaluation of pooled data showed that the response of Saanen goats to treatments was comparable to the results of other published trials. Results of this study indicate that administration of GnRH at 24 h or 36 h after sponge removal, at the end of a short estrus induction and synchronization protocol, does not affect plasma P4 and E2 concentrations, estrus parameters and ovulation time in goats, during the transition period.